2021
DOI: 10.3389/fbioe.2021.615090
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Identification of High-Risk Patients Requiring Permanent Pacemaker After Transcatheter Aortic Valve Replacement

Abstract: BackgroundCardiac conduction disturbance requiring new permanent pacemaker implantation (PPI) is an important complication of TAVR that has been associated with increased mortality. It is extremely challenging to optimize the valve size alone to prevent a complete atrioventricular block (AVB).MethodsIn this study, we randomly took 48 patients who underwent TAVR and had been followed for at least 2 years to assess the risk of AVB. CT images of 48 patients with TAVR were analyzed using three-dimensional (3D) ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Therefore, it is difficult to judge a DCMP directly from original medicine images. In order for the cardiologist to achieve correct diagnosis, the echocardiogram images have to be despeckled [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is difficult to judge a DCMP directly from original medicine images. In order for the cardiologist to achieve correct diagnosis, the echocardiogram images have to be despeckled [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, pretreatments (standard normal variation (SNV), multiple scatter correction (MSC), first derivative (FD), and Savitzky–Golay filtering (SG)) were performed, and the transformed spectra showed a more diverse variation than the raw spectra ( Supplementary Figure S1 ). Previous studies found that a support vector machine regression (SVR) model is suitable for the prediction of a relatively small sample size, and SVR has been widely used in VIS/NIR models [ 22 , 23 ]. In this study, four models showed high determination coefficients (R 2 ) (>0.95) in the calibration dataset.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, the pressure distribution of the device landing zone is mainly simulated and predicted via preoperative finite element analysis [ 9 ], and there is no evaluation method for the actual pressure after implantation. In a previous study, the vast majority of implanted valve frames suffered from some degree of compression [ 10 ].…”
Section: Discussionmentioning
confidence: 99%